Tumor cell-derived EMP1 is essential for cancer-associated fibroblast infiltration in tumor microenvironment of triple-negative breast cancer - Qi Wang; Dandan Li; Haixiu Ma; Zengyan Li; Juan Wu; Jinwan Qiao; Jun Liu; Jing Zhao; Ronghua Ma; Lin Tian; Lei Zhang; Jianye Yang; et al. (Cell Death and Disease)
Abstract The role of epithelial membrane protein 1 (EMP1) in tumor microenvironment (TME) remodeling has not yet been elucidated. In addition, the biological function of EMP1 in triple-negative breast cancer (TNBC) is largely unclear. In this study, we examined the infiltration landscape of cell types in the TME of breast cancer, and found that EMP1 expression was positively correlated with stromal and microenvironmental scores. Infiltration analysis and immunohistochemical (IHC) staining of serial sections confirmed the critical role of EMP1 in cancer-associated fibroblast (CAF) infiltration. Cell co-culture assays, xenograft tumor experiments, loss-of-function, gain-of-function, RNA sequencing studies, and rescue assays were performed to confirm the role of EMP1 in CAF infiltration in vitro and in vivo. These findings revealed that EMP1 depletion in TNBC cells resulted in considerable inhibition of CAF infiltration in vivo and in vitro. Mechanistically, EMP1 knockdown induced a substantial decrease in IL6 secretion from TNBC through the NF-κB signaling pathway, hindering CAF proliferation and subsequently inhibiting TNBC progression and metastasis. These cumulative results indicate that EMP1 functions as an oncogene in TNBC by mediating the cell communication of TNBC and CAFs. Targeted inhibition of EMP1 by suppressing CAF infiltration is a promising strategy for TNBC treatment.